Enhancing EFL Learners’ Writing Performance Through Project-Based Learning: Evidence from Moroccan Secondary Education - Hind Maalfi; Hind Brigui (Yayasan Visi Intan Permata, 2026)
Writing is considered by a wide range of EFL learners to be the most difficult component to learn. Achievement on this component tends to be the lowest among the other language skills. Educators have been concerned with adopting the latest teaching strategies which could yield better results in students’ writing. Interestingly, project-based learning (PjBL) seems to be an effective approach in improving learners’ writing skills. The current quasi-experimental research seeks to examine the effectiveness of PjBL on students’ writing in EFL classes. This study targeted common core students as its population. The sample involved an experimental group consisting of 34 participants and a control group consisting of 33 participants. The groups were randomly assigned to an experimental group undergoing the PjBL treatment or a control group with no treatment. Data was collected through a writing pretest and posttest, and was analyzed using the SPSS software. After establishing a normal distribution of the scores, an Independent Samples T-test was run. The pretest results show that both groups had an equal departure. The posttest results show a significant difference in the means of both groups, with the experimental group scoring significantly higher. The results confirm that PjBL is an efficient tool to promote the acquisition of writing skills in EFL classes. This is thanks to the nature of the approach, which involves learners in different engaging phases throughout the project. Therefore, and based on the results, this approach appears to deserve more attention n and consideration from the part of curriculum designers.